THE SELF-REGULATION FEATURES OF FUSION OF AN ELECTRODE - V. A. LENIVKIN; D. V. KISELYOV (Advanced Engineering Research, 2010)
Features of self-regulation of electrode wire fusion under the machine welding in the protective environment of argon and argon mixtures are investigated.The mechanism of cyclic changes in the current and arc voltage is revealed.Ways of stabilization of electrode fusion through the application of rigid static characteristics of feeding system and increase of the positive slope of the static characteristics of the arch are defined.